Operational Load on Material Handling Process Stockyard Ship to Port Using Field Tests - Sunarso Sugeng; Mohammad Ridwan; Samuel Febriary Khristyson (Diponegoro University, 2026)
Since all equipment needs to be handled correctly, the equipment handling procedure is crucial. in order to ensure the equipment's safe arrival at its destination and to preserve its quality and condition. The method used in this research to analyze the calculation using experiment set with sensor data and observation. Finding the optimal operational load process value during material loading and unloading at the Panjang Port is the aim of this study. From analyze results horizontal direction movement speed of 2 km/h has a pressure value of 37 kPa with a distance of 376 mm from the center end of the pipe being unloaded, across the stress value is at 167 kPa with a stretch distance of less than 300 mm, longitudinal direction of 45 kPa.